Isolation of Theileria parasites from African buffalo (Syncerus caffer) and characterization with anti-schizont monoclonal antibodies - Conrad, P.A.; Stagg, D.A.; Grootenhuis, J.G.; Irvin, A.D.; Newson, J.; Njamunggeh, R.E.G.; Rossiter, P.B.; Young, A.S. (Cambridge University Press, 1987)
Antigenic differences between intra-lymphocytic theilerial parasites isolated from the blood of 18 African buffalo and grownin vitrowere assessed with anti-schizont monoclonal antibodies (mAbs). There was marked antigenic diversity both between isolates from different buffalo and between isolates taken at different times from the same buffalo. Many of the isolates from both wild and captive buffalo appeared to consist of mixed parasite populations. Some isolates were found by limiting dilution cloning and mAb testing to contain at least 3 or 4 distinct populations ofTheileria. Once cloned,Theileria-infected lymphoblastoid cell lines retained their mAb profiles during prolongedin vitrocultivation and, when recloned, the subclones had the same mAb profile as their parent clone. The implications of these results for further studies on buffalo-derived theilerial parasites are discussed.